Internet and consumer privacy: Considering the FTC's do not track proposal - Ralf Boscheck (Intereconomics, 2011)
The digital economy relies on the collection of personal data on an ever-increasing scale. Regulations have to be found which can provide an optimal balance between consumers' interest in privacy and the benefits from innovations that rely on the largely invisible collection, retention and sharing of consumer data. The following article discusses current US reform proposals and their relevance for the ongoing debate in Europe.
Keywords: 330